(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines how, under the influence of unfavorable climatic, hydrological, man-made and other factors, destabilizing processes occur in the soils of the body of the roadbed, which cause residual deformations of the main site and slopes of the roadbed.